2020
DOI: 10.3390/jcm9123864
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Levothyroxine-Treated Hypothyroid Women and Women without Hypothyroidism: A Case–Control Study

Abstract: The use of levothyroxine is not always related to the elimination of the symptoms of hypothyroidism. The aim of this study is to compare the health-related quality of life (HRQOL) of a group of hypothyroid women under levothyroxine treatment with that of a group of non-hypothyroid women. Methodology: A case–control study was performed. We used convenience sampling. The case group consisted of 152 levothyroxine-treated hypothyroid women; the control group consisted of 238 women without hypothyroidism disorders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
0
12
1
Order By: Relevance
“…The current study concluded that an individual's overall mental health is strongly influenced by two major factors, one of them being smoking. This finding is contrary to those of a previous study that suggested that tobacco consumption had no connection with the HRQoL in women with hypothyroidism [ 16 ]. In concordance with the findings of Morón-Diaz et al (2021), our data demonstrated an association between QOL and cigarette consumption [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current study concluded that an individual's overall mental health is strongly influenced by two major factors, one of them being smoking. This finding is contrary to those of a previous study that suggested that tobacco consumption had no connection with the HRQoL in women with hypothyroidism [ 16 ]. In concordance with the findings of Morón-Diaz et al (2021), our data demonstrated an association between QOL and cigarette consumption [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A compatible study revealed that HRQoL was affected by hypothyroidism [ 16 ]. Another study that evaluated the potential association between hypothyroidism and QoL in relation to BMI, revealed that patients with hypothyroidism have impaired QoL and experienced more problems with physical functioning [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of levothyroxine is not constantly linked to the disappearance of hypothyroidism symptoms. The goal of this survey is to evaluate the health-linked quality of life (HRQOL) of hypothyroid ladies treated with levothyroxine to that of nohypothyroid ladies [2]. Objective In premenopausal women, even modest hypothyroidism causes problems with sexual function.…”
Section: Treatmentmentioning
confidence: 99%
“…The goal of the study was to see how levothyroxine, given alone or in conjunction with liothyronine, affected sexual function and depressed signs in premenopausal ladies who were being given for hypothyroidism. Methods This single-blind, quasi-randomized experimental included 39 young ladies who were taking levothyroxine and had clinical symptoms of hypothyroidism despite having normal thyrotropin and thyroid hormone levels [2].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation